Bridging osteophyte of the anterosuperior sacroiliac joint as a cause of lumbar back pain. Issue 6 (23rd November 2004) - Parmar, K A; Solomon, M; Loefler, A; Dalton, S
Abstract : A case report is presented of a patient with an anterosuperior osteophytic bone bridge of the sacroiliac joint causing lumbar back pain. After prolonged physiotherapy, the bone bridge was excised, with complete resolution of the symptoms. Excision should only be considered in cases of symptomatic sacroiliac joint pain that does not respond to rehabilitation programmes and conservative treatment.